2021
DOI: 10.3390/app11031034
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of NaCl Stress in Wheat by Rhizosphere Engineering Using Salt Habitat Adapted PGPR Halotolerant Bacteria

Abstract: There is a great interest in mitigating soil salinity that limits plant growth and productivity. In this study, eighty-nine strains were isolated from the rhizosphere and endosphere of two halophyte species (Suaeda mollis and Salsola tetrandra) collected from three chotts in Algeria. They were screened for diverse plant growth-promoting traits, antifungal activity and tolerance to different physico-chemical conditions (pH, PEG, and NaCl) to evaluate their efficiency in mitigating salt stress and enhancing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 57 publications
3
41
0
1
Order By: Relevance
“…Soil salinization is becoming a major problem in multiple regions around the world. It is affected by numerous factors, including climate changes and uncontrolled anthropogenic activities by the continuously increasing human population [1,2]. The extent of land salinization is determined by measuring the level of pH, certain ions' (Na + , Ca 2+ , SO 4 2− , K + , SO 4 2− , Cl − , and Mg 2+ ) accumulation, and electrical conductivity (>4 dSm −1 ) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Soil salinization is becoming a major problem in multiple regions around the world. It is affected by numerous factors, including climate changes and uncontrolled anthropogenic activities by the continuously increasing human population [1,2]. The extent of land salinization is determined by measuring the level of pH, certain ions' (Na + , Ca 2+ , SO 4 2− , K + , SO 4 2− , Cl − , and Mg 2+ ) accumulation, and electrical conductivity (>4 dSm −1 ) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Their identification, isolation, molecular classification and possessing relevant PGP features are essential for moving towards an agriculture more respectful of agroecosystems and consequently of human and animal health [52]. As stated above, salinization is one the main problem afflicting agricultural soils, however PGPRs can be of great help in reducing the impact of soil salinization and, at the same time, improving crop productivity and health [53,54]. The bacterial strains, we isolated and taxonomically classified in this research work, showed tolerance to very high NaCl concentrations, but also several PGP features, demonstrating, once more, that compost amendment of soil not only increases its fertility, but it is also a valuable source of rhizosphere bacteria able to promote health, resilience and plant productivity.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3 , the isolated IAA-producing microbes significantly enhanced plant growth in biomass under the simulated saline condition in terms of shoot length and weight (fresh and dry), emphasizing root length and weight (fresh and dry), and germination rates of salt-sensitive crop seeds. Furthermore, the selected microbes will have a slight improvement to no significant effects on non-stressed control plants [ 63 , 104 , 114 , 115 ].…”
Section: Plant Growth-promoting Mechanisms By Ht-pgpbmentioning
confidence: 99%